2018
DOI: 10.3390/ma11101995
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Microelectrodes in Neural Interfaces

Abstract: Brain‒machine interface (BMI) is a promising technology that looks set to contribute to the development of artificial limbs and new input devices by integrating various recent technological advances, including neural electrodes, wireless communication, signal analysis, and robot control. Neural electrodes are a key technological component of BMI, as they can record the rapid and numerous signals emitted by neurons. To receive stable, consistent, and accurate signals, electrodes are designed in accordance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 178 publications
(208 reference statements)
1
77
0
Order By: Relevance
“…Recent advancement in the microelectronics manufacturing promoted the development of patterned, micromachined, and rigid probes [46]. Nowadays, the state-of-the-art devices like Michigan-style probes [47] and Utah arrays [48] are commercially available and has been utilized in neuroscience research. Furthermore, emerging Silicon-based implantable probe technologies such as Neuropixels for high-density neural recordings [49], multifunctional probe [50], as well as 3D probe for recording of coordinated brain activity from large population of neurons [51] have enriched us with new insights to study the brain.…”
Section: A Equivalent Circuit Analysis Of the Probe/tissue Interfacementioning
confidence: 99%
“…Recent advancement in the microelectronics manufacturing promoted the development of patterned, micromachined, and rigid probes [46]. Nowadays, the state-of-the-art devices like Michigan-style probes [47] and Utah arrays [48] are commercially available and has been utilized in neuroscience research. Furthermore, emerging Silicon-based implantable probe technologies such as Neuropixels for high-density neural recordings [49], multifunctional probe [50], as well as 3D probe for recording of coordinated brain activity from large population of neurons [51] have enriched us with new insights to study the brain.…”
Section: A Equivalent Circuit Analysis Of the Probe/tissue Interfacementioning
confidence: 99%
“…Indeed, stiffness mismatch between the brain tissue and the probe substrate represents the main cause of implant failure. Brain is relatively soft with a Young's Modulus of few kPa, while even flexible MEAs based on polyimide, SU-8 or Parylene are in the range of few GPa [10]. Conversely, soft polymers like PDMS show similar brain stiffness but result difficult to handle and cannot be easily manufactured in ultra-thin layers.…”
Section: Neural Interfacementioning
confidence: 99%
“…Numerous review papers reported new findings in the part that is usually in contact with the brain, such as the electrode grid [10][11][12][13] and described physiological mechanisms underlying the implantation of these devices in the brain [14], but very few present all the fabrication methodologies that involve new materials and electronic design to allow the manufacturing of the whole system.…”
Section: Introductionmentioning
confidence: 99%
“…Subdural electrodes are much less invasive than penetrating depth electrodes that cause tissue damage and elicit pronounced foreign body response . At the same time, subdural electrodes can record neural activity with higher temporal and spatial resolution than scalp electrodes because of their close proximity to neural tissues . For these reasons, subdural ECoG recordings have also been considered as an attractive candidate to build next‐generation brain‐machine interface (BMI) …”
Section: Introductionmentioning
confidence: 99%
“…The interfaces between electrodes and neural tissues play an essential role in neural activity recordings because extracellular signals decay rapidly with distance . A key challenge for creating tight interfaces between conventional subdural electrodes and neural tissues has been their large mechanical mismatch .…”
Section: Introductionmentioning
confidence: 99%